2016
DOI: 10.1177/0192623316649258
|View full text |Cite|
|
Sign up to set email alerts
|

Maturity-related Variability of the Thymus in Cynomolgus Monkeys (Macaca fascicularis)

Abstract: Terminal body weights (TBWs), thymus weight parameters, and thymus morphology were retrospectively evaluated in 453 cynomolgus monkeys assigned to control groups on nonclinical toxicity studies. Morphology of bone, ovary, and testis/epididymis were used to determine maturity status of individual animals. There was no correlation between TBW and thymus weight (absolute and/or relative to TBW or brain weight). Thymus weight parameters and grades of decreased lymphocytes in the thymus were highly variable in imma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 63 publications
3
11
0
Order By: Relevance
“…Terms used for light microscopic observations in this study were generally descriptive rather than diagnostic, with the exception of the use of terms historically applied to findings resulting from hemoparasitism (reticuloendothelial [RE] hyperplasia and malarial pigment). This companion study expands on the understanding of the variability of the cynomolgus monkey immune system that was previously described for the thymus (Snyder et al 2016). In addition, this study extends and refines previously published observations of incidental background observations in the spleen (Chamanza et al 2010;Ito et al 1992;Okazaki et al 1996;Kaspareit et al 2006;Spoor, Radi, and Dunstan 2008;McInnes 2011) and MLN (Chamanza et al 2010), providing a detailed evaluation of the range of light microscopic observations with comparisons to other study results.…”
supporting
confidence: 80%
See 2 more Smart Citations
“…Terms used for light microscopic observations in this study were generally descriptive rather than diagnostic, with the exception of the use of terms historically applied to findings resulting from hemoparasitism (reticuloendothelial [RE] hyperplasia and malarial pigment). This companion study expands on the understanding of the variability of the cynomolgus monkey immune system that was previously described for the thymus (Snyder et al 2016). In addition, this study extends and refines previously published observations of incidental background observations in the spleen (Chamanza et al 2010;Ito et al 1992;Okazaki et al 1996;Kaspareit et al 2006;Spoor, Radi, and Dunstan 2008;McInnes 2011) and MLN (Chamanza et al 2010), providing a detailed evaluation of the range of light microscopic observations with comparisons to other study results.…”
supporting
confidence: 80%
“…When the geographic origin of animals could not be determined from study reports, peripheral blood mean cell volume data were used to assign origin, as monkeys from Mauritius have smaller red blood cells than monkeys from China or Southeast Asia (Butterfield 1997). Although the vast majority of the animals included in this study were also included in a previous manuscript assessing thymus parameters (Snyder et al 2016), the final set of monkeys was not identical because inclusion was dependent on availability of spleen with or without MLN sections for this study and the availability of thymus sections and weights for the previous study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the structure and the function are closely related, the microstructure of different aged thymuses was explored by HE staining that showed a downtrend, except for a small increase at the 3 rd week, with significant alterations in ratio of the cortex to medulla. Similar changes in the aging thymus were also previously reported in rats [4143], African ostrich chicks [44, 45], and cynomolgus macaques [46, 47]. In addition, we also found an accumulation of adipose tissue while aging.…”
Section: Discussionsupporting
confidence: 90%
“…The blockade was not observed with increasing pembrolizumab dose, suggesting that tracer distribution in the thymus was not PD-1-mediated. This was not unexpected, since there is a progressively decrease in the number of cortical lymphocytes during age-related thymus involution from about 4 or 5 years old in cynomolgus monkeys [24], and the monkeys in this study were over 7 years of age. Additionally, few studies have reported thymic uptake of radiopharmaceuticals assessing receptor expression on immune cells as a result of dramatic thymic function changes [25]; therefore, the 89 Zr-N-sucDf-pembrolizumab retention in the thymus of monkeys over 5 years old is not considered to be a relevant organ to track the distribution of PD-1-positive immune cells.…”
Section: Discussionsupporting
confidence: 63%